2008
DOI: 10.1074/jbc.m708943200
|View full text |Cite
|
Sign up to set email alerts
|

The Inactive 44-kDa Processed Form of Membrane Type 1 Matrix Metalloproteinase (MT1-MMP) Enhances Proteolytic Activity via Regulation of Endocytosis of Active MT1-MMP

Abstract: Membrane type 1 (MT1) matrix metalloproteinase (MMP-14)is a membrane-tethered MMP considered to be a major mediator of pericellular proteolysis. MT1-MMP is regulated by a complex array of mechanisms, including processing and endocytosis that determine the pool of active proteases on the plasma membrane. Autocatalytic processing of active MT1-MMP generates an inactive membrane-tethered 44-kDa product (44-MT1) lacking the catalytic domain. This form preserves all other enzyme domains and is retained at the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 82 publications
2
26
0
1
Order By: Relevance
“…In all cases, the degree of MMP-2 activation was concomitant with the level of the truncated MT1-MMP form [28]. As it has been demonstrated that the~4 5-kDa truncated MT1-MMP form is derived from proteolytic degradation of the~60-kDa active form by self-cleavage or by active MMP-2 [29], these results further confirm that CD97 expression in HT1080 cells inhibits the activation of MT1-MMP and MMP-2.…”
Section: Cd97 Inhibits Cell Migration/invasion In Vitro and Suppressesupporting
confidence: 73%
“…In all cases, the degree of MMP-2 activation was concomitant with the level of the truncated MT1-MMP form [28]. As it has been demonstrated that the~4 5-kDa truncated MT1-MMP form is derived from proteolytic degradation of the~60-kDa active form by self-cleavage or by active MMP-2 [29], these results further confirm that CD97 expression in HT1080 cells inhibits the activation of MT1-MMP and MMP-2.…”
Section: Cd97 Inhibits Cell Migration/invasion In Vitro and Suppressesupporting
confidence: 73%
“…It should be noted that the increase in MMP-14 activity was not due to an increased amount of MMP-14 at the mRNA or protein level, but relies on its appropriate localization at the plasma membrane in accordance with earlier findings (Seiki 2003). Processing of MMP-14 at the cell surface is an event in which the active MMP-14 proteinases is autocatalytically cleaved to generate a membrane-anchored fragment of 43 kDa and a soluble 18 kDa inactive fragment of the catalytic domain (Cho et al, 2008;Ellerbroek et al, 2001;Itoh, 2006). Here, we detected the 43 kDa MMP-14 fragment in both tumor cell and tumor tissue extracts, further demonstrating that MMP-14 was present in an active form.…”
Section: Adam12 Activates Mmp-14 4715supporting
confidence: 69%
“…7D). To evaluate the influence of ADAM12 on MMP-14 activation, we analyzed the level of the partially autodigested 43 kDa fragment of MMP-14, which is indicative of active MMP-14 (Cho et al, 2008;Ellerbroek et al, 2001;Itoh, 2006), by western blotting (Fig. 7E).…”
Section: Adam12 Decreases the Apoptotic Capacity Of Breast Tumor Cellmentioning
confidence: 99%
“…Although the specific roles of secreted collagenases and MT-MMPs were not evaluated directly in their work, RA synoviocyte invasion was inhibited when cells were infected with an adenoviral vector encoding a MT1-MMP dominant-negative fragment previously reported to interfere with the catalytic activity of the wild-type enzyme (53). At this juncture, however, the utility of this indirect approach for implicating MT1-MMP can only be embraced cautiously because given that others have reported that the MT1-MMP fragment enhances, rather than inhibits, MT1-MMP proteolytic activity (54). Further, the possibility that the MT1-MMP dominant-negative construct exerts more complex effects on cell function by sequestering signaling molecules that normally bind to the MT1-MMP cytosolic tail has not yet been evaluated (55).…”
Section: Discussionmentioning
confidence: 97%